PENERAPAN PERIZINAN TERPADU DALAM PENERBITAN IZIN LINGKUNGAN DI PROVINSI SUMATERA UTARA (Studi: Izin Lingkungan PT. Arah Environmental) - Radinal Panggabean; Suhaidi Suhaidi; Syamsul Arifin; Pendastaren Tarigan (USU LAW JOURNAL, 2015)
ABSTRACT Environmental protection and management need an integrated system to be developed. This system is a national policy in environmental protection and management which has to be done consistently and consequently from the central government to local government in permits. North Sumatera Provincial Administration has the Integrated Permit Service Board which one of its authorities is issuing environment permit as the requirement to get business/activity license which is regulated based on the prevailing rules. PT. Arah Environmental is a company which operates in the field of hospital medical waste gathering. Before it gets its business license, it has to complete environment permit first. The latter is issued, based on environmental feasibility and recommendation from UKL-UPL which is used as the instrument for planning preventive action against environmental pollution and damage which has possibly been caused by business/activity. It could be concluded that coordination among regional government agencies was needed. Even though integrated permit is considered a good system, it does not guarantee its implementation of forestalling environmental pollution and damage as the result of business or activity implementation.   Keywords:      Integrated Permits, Integrated Permit Service Board, Environment Permit